Spiritualitas di Era Digital - Ridwan Henry Simamora; Eliasar Lekitonu; Deiby Betsy Najoan (Sekolah Tinggi Teologi SAPPI Ciranjang, 2026)
Abstract The rapid development of digital technology has transformed not only social and economic life but also the spiritual practices of contemporary society. This study examines the emergence of digital spirituality and its influence on Christians’ understanding and experience of faith in the digital era. Using a descriptive method with a library research approach, the study explores the opportunities and challenges of spirituality within digital contexts while highlighting technology’s role as a medium for spiritual formation. The findings indicate that social media functions not only as a tool for ministry but also as a theological and existential space that shapes how Christians understand, experience, and express their faith. Consequently, churches are encouraged to develop a contextual, critical, and transformative digital spirituality that enables technology to support discipleship, character formation, and the strengthening of Christian communities while maintaining the authenticity of faith in an increasingly digitalized world.